The Republic of Chile Systematic Country Diagnostic : Transitioning to a Prosperous Society - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
Three key characteristics help shed light on Chile’s development performance. First, strong institutions and sound macroeconomic policies have contributed to long-term economic growth. Second, market-oriented policies have boosted growth through productivity-enhancing reforms and helped improve the design of public services and social policy. Third, as the world’s biggest copper producer and exporter, Chile is characterized by commodity dependence. These characteristics have helped the government achieve an average annual growth rate of almost 5 percent over the last 30 years, while reducing the poverty rate to less than 8 percent. Chile’s middle class is one of the largest in Latin America; yet, inequality remains substantial. Economic development has led to a steep increase in life expectancy and a decline in fertility rates. Indeed, though relatively less than other countries in the Organisation for Economic Co-operation and Development (OECD), Chile is advanced in the demographic transition, which pose important challenges to economic growth and labor productivity.